2005
DOI: 10.1627/jpi.48.76
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> Reforming of Methane on Ni- and Co-based Intermetallic Compound Catalysts

Abstract: Catalytic properties of Ni-and Co-based intermetallic compound (IMC) were assessed for the CO2 reforming of methane. Single-phase IMCs were prepared by arc-melting mixtures of stoichiometric amounts of nickel or cobalt and a second element. IMCs were crushed into particles and used as a catalyst for the CO2 reforming of methane at 1073 K. Ni-and Co-IMCs containing Ta, Hf and Sc showed higher initial activity than Ni and Co powders. Stability of these IMCs was examined for the reaction at 923 K because lower te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…39 In a similar fashion, the stability of different Hf-based intermetallic compounds (e.g., NiHf or CoHf 2 ) during dry reforming has been assessed. 40 The same concept of creating supported-metal catalysts via decomposition of precursor structures was previously discussed for amorphous metal alloys (i.e., "metal glasses"). Several examples in the literature exist, which have demonstrated the potential to use such materials as promising catalyst precursors.…”
Section: Introduction Into the Scientific Conceptmentioning
confidence: 93%
See 2 more Smart Citations
“…39 In a similar fashion, the stability of different Hf-based intermetallic compounds (e.g., NiHf or CoHf 2 ) during dry reforming has been assessed. 40 The same concept of creating supported-metal catalysts via decomposition of precursor structures was previously discussed for amorphous metal alloys (i.e., "metal glasses"). Several examples in the literature exist, which have demonstrated the potential to use such materials as promising catalyst precursors.…”
Section: Introduction Into the Scientific Conceptmentioning
confidence: 93%
“…A recent study on Ni–Y alloys also revealed in situ decomposition into Ni/Y 2 O 3 composites with superior dry reforming activity . In a similar fashion, the stability of different Hf-based intermetallic compounds (e.g., NiHf or CoHf 2 ) during dry reforming has been assessed …”
Section: Introduction Into the Scientific Conceptmentioning
confidence: 94%
See 1 more Smart Citation
“…As a reaction related to CO x reduction, they also tested the application of Ni- and Co-based intermetallic compounds to CO 2 reforming of methane. Among the various unsupported intermetallic compounds, CoHf 2 exhibited 8- and 2.5-fold higher CO 2 conversions than monometallic Co and Ni, respectively at 750 °C . CoHf 2 also showed long-term stability of CO 2 conversion over 100 h, whereas that of monometallic Ni declined to half over the same time.…”
Section: Survey Of Intermetallic Catalystsmentioning
confidence: 99%
“…The CO 2 reforming of methane was studied on Ni-and Cobased unsupported IMC catalysts with the continuous flow reactor under atmospheric pressure [33]. Among various IMCs, those with Ta, Hf and Sc were more active than pure Ni and Co. Because the CO 2 reforming is always accompanied by the severe coke formation to shorten the catalyst life, the reaction was carried out for 24 h on these active IMCs to obtain the rate of deactivation and the amount of coke.…”
Section: Co 2 Reforming Of Methanementioning
confidence: 99%